Nothingness and the Scene of Representation: East and West - Gans, Eric Lawrence (2024)
I As the Western-centered world order established after WWII appears to be losing its grip, most significantly in the West itself, considerations of "scholarship" and "theory" can no longer be pursued as if in the context of a civilization confident of self-perpetuation. As GA makes clear, the underlying purpose of language, religion, and all the...